2005
DOI: 10.1620/tjem.206.131
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of N-Acetylcysteine on Acetic Acid-Induced Colitis in Rats

Abstract: Ulcerative colitis is a chronic recurrent inflammatory bowel disease in which oxidative stress has been implicated. The aim of the present study was to evaluate possible protective effects of N-acetylcysteine against acetic acid-induced colitis in a rat model. Rats were administered intrarectal saline (control group) or acetic acid (colitis model group). Rats with acetic acid-induced colitis were treated by intraperitoneal or intrarectal administration of N-acetylcysteine (500 mg/ kg) (treated group). Another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
86
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 42 publications
17
86
0
2
Order By: Relevance
“…When considering that the use of substances with antioxidant activity can neutralize the harmful effects of OFRs, it becomes an interesting strategy for the treatment of diseases related to oxidative stress. Studies conducted in experimental models of chemically induced colitis confirmed the beneficial effects of antioxidants, improving the inflammatory process of colonic mucosa [27][28][29][30][31] . Several drugs have been tested with effective results in experimental conditions, including 5-ASA, glucocorticoids, L-carnitine, L-glutamine, melatonin and antioxidants found in the aqueous extract of Ilex paraguariensis and Curcuma longa [33][34][35][36][37][38][39] .…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…When considering that the use of substances with antioxidant activity can neutralize the harmful effects of OFRs, it becomes an interesting strategy for the treatment of diseases related to oxidative stress. Studies conducted in experimental models of chemically induced colitis confirmed the beneficial effects of antioxidants, improving the inflammatory process of colonic mucosa [27][28][29][30][31] . Several drugs have been tested with effective results in experimental conditions, including 5-ASA, glucocorticoids, L-carnitine, L-glutamine, melatonin and antioxidants found in the aqueous extract of Ilex paraguariensis and Curcuma longa [33][34][35][36][37][38][39] .…”
Section: Discussionmentioning
confidence: 82%
“…It is filterable and easily crosses the cellular membranes, with easy access to different intracellular compartments 29 . NAC has been used as an antioxidant both in vivo and in vitro, in different situations 29,30 and it has been used in clinical practice to treat several diseases, including pulmonary disorders caused by excess oxygen, against the paracetamol toxic effects, infection of human immunodeficiency virus, and the treatment of disorders caused by ischemia in liver, lungs and skin flaps 37,40,41 . The possibility of different pharmacological applications is regulated by the chemical properties of the group of thiol-cysteine molecules to eliminate OFRs 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAC has been widely used both in vitro and in vivo as an antioxidant (6) . It is also efficient in the treatment of some pharmacological overdoses, as in the one caused by paracetamol (28) .…”
Section: Introductionmentioning
confidence: 99%